PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING TERHADAP MOTIVASI DAN PRESTASI BELAJAR MAHASISWA ( Studi Eksperimen pada Mata Kuliah Komputasi Paralel Mahasiswa Angkatan III Program Studi Teknik Informatika di FKOM UNIKU ) - Nita Mirantika (NUANSA INFORMATIKA, 2013)
The presence of parallel computing courses in Informatics Engineering program is very relevant, applicable and can provide great inspiration for learners. But in reality, this parallel computing courses many students complain because the perceived difficult to learn. Course materials are always on the up grade in accordance with the technological developments that are in. Conventional teaching methods are still the favorite method is given, can not be a good solution to the above problems. because conventional study focused only on the educators in this faculty, so that students are passive, not pushing for creative thinking. Therefore we need another method, which can provide insight and inspiration to the students so that learning can take place effectively and in accordance with technological developments. One of these alternatives is the use of e-learning media.To assess the use of e-learning media are expected to be an alternative solution to the above problems, the authors conducted a study on Information Technology Student III level UNIKU who took a course parallel computing using three classes. The method used is the experimental method. With a variety of considerations, which became the experimental class is TI A class and TI C while the control class is TI B class. Data research conducted through written tests and questionnaires. Data were analyzed using a computerized program SPSS version 16 at the level of 95%. The results showed that the use of e-learning media can increase student motivation and achievement compared to conventional learning.  Keywords: E-learning, Learning Media, Experimental Study, learning motivation, learning achievement.